2010
DOI: 10.2134/jeq2009.0440
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Eutrophication on the Distribution of Total Mercury and Methylmercury in Hydroelectric Reservoirs

Abstract: The distribution of mercury (Hg) and the characteristics of its methylation were investigated in Wujiangdu (WJD) and Yinzidu (YZD) reservoirs in Guizhou province, China. The two reservoirs are characterized by high and low levels of primary productivity, respectively. Mercury species in water samples from depth profiles in both reservoirs and from interface water in the WJD were analyzed each season during 2007. The concentrations of total Hg (HgT(unf)) and methylmercury (MeHgT(unf)) in unfiltered water sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…As many researchers have shown, atmospheric deposition of Hg depends upon Hg speciation; highly soluble Hg 2+ species are quickly stripped from the atmosphere and deposited locally, whereas PHg emissions are transported regionally, and elemental emissions are transported globally (Demers et al 2007;Porvari and Verta 2003). On the issue of atmospheric transport and deposition at this study area, which are described in detail in BPotential source identification for transport of atmospheric Hg^section, RHg concentration in litterfall of the study area was slightly higher compared with other studies (Meng et al 2011); no obvious Hg activation effect was observed.…”
Section: Resultsmentioning
confidence: 53%
“…As many researchers have shown, atmospheric deposition of Hg depends upon Hg speciation; highly soluble Hg 2+ species are quickly stripped from the atmosphere and deposited locally, whereas PHg emissions are transported regionally, and elemental emissions are transported globally (Demers et al 2007;Porvari and Verta 2003). On the issue of atmospheric transport and deposition at this study area, which are described in detail in BPotential source identification for transport of atmospheric Hg^section, RHg concentration in litterfall of the study area was slightly higher compared with other studies (Meng et al 2011); no obvious Hg activation effect was observed.…”
Section: Resultsmentioning
confidence: 53%
“…Wujiangdu and Yinzidu Reservoir;Feng et al, 2009aFeng et al, , 2009bMeng et al, 2010b). Furthermore, total-Hg concentrations in the Hongfeng Reservoir impacted by a coal-fired power plant were elevated and slightly increased with depth in water columns (He et al, 2008a(He et al, , 2008b.…”
Section: Lakes and Reservoirsmentioning
confidence: 99%
“…However, to an increasing extent the reservoirs are affected by human activities, such as the cage aquaculture, that significantly add to organic matter in the sediment over time, feasibly stimulating the process of methylation. Feng et al (2009aFeng et al ( , 2009b and Meng et al (2010b) demonstrated that the primary productivity and also the water residence time are important factors that control the potential of net Hg methylation in the Wujiang River reservoirs. Compared to lakes and reservoirs located at higher latitudes, the premises and evolution of methylation in Chinese hydropower reservoirs appear different.…”
Section: Lakes and Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Amazon region, mercury levels are of even greater concern, in this particular region when factored with the effects of a hydroelectric facility being constructed in the area, and continued gold mining in the region (Meng, 2010).…”
Section: Introductionmentioning
confidence: 99%